Uji Prototype Metode Design Thinking pada Penyebaran Informasi COVID-19 - Rofi Abul Hasani; Muhammad Resa Arif Yudianto; Pristi Sukmasetya; Yusril Febriyanto (Lembaga Penelitian, Pengabdian Kepada Masyarakat dan Publikasi (LPPMP), 2022)
The spread of information about COVID-19 spreads so fast that the information circulating in the community has not been confirmed. This causes excessive anxiety and fear. There are several approaches to getting things done like design thinking, design sprint, and lean UX. With the right approach, this kind of situation will be resolved. From these problems, in this research, problem-solving will be carried out using a design thinking method. Because design thinking is the best method for developing innovative products. The design thinking process consists of 5 stages: Empathize, Define, Ideate, Prototype, Test. This research has carried out all these stages. The prototyping process uses the Figma mirror application to produce a more real experience for users. Then the prototype was tested on 5 respondents. After the test is carried out, it shows the success data based on predetermined indicators in the form of task 1 success is 80%, task 2 success is 100% successful, task 3 success is 60%, task 4 success is 40%, task 5 success is 100% and task 6 has 60% success. so that the average success of the prototype made is 88%. This means that the prototype developed with the design thinking method is easy for users to use. However, there are still features that have a low yield of 40%. So in the next iteration, it is necessary to improve the interface display that focuses on the call doctor feature based on user feedback.